Effectiveness of the Korean National Cancer Screening Program in Reducing Gastric Cancer Mortality - Jun, Jae Kwan; Choi, Kui Son; Lee, Hoo-Yeon; Suh, Mina; Park, Boyoung; Song, Seung Hoon; Jung, Kyu Won; Lee, Chan Wha; Choi, Il Ju; Park, Eun-Cheol; Lee, Dukhyoung (Gastroenterology (New York, N.Y. 1943), 2017)
It is not clear whether screening for gastric cancer by upper endoscopy or upper gastrointestinal (UGI) series examinations (looking at the upper and middle sections of the gastrointestinal tract by imaging techniques) reduces mortality. Nevertheless, the Korean National Cancer Screening Program for gastric cancer was launched in 1999 to screen individuals 40 years and older for gastric cancer using these techniques. We evaluated the effectiveness of these techniques in gastric cancer detection and compared their effects on mortality in the Korean population. We performed a nested case−control study using data from the Korean National Cancer Screening Program for gastric cancer since 2002. A total of 16,584,283 Korean men and women, aged 40 years and older, comprised the cancer-free cohort. Case subjects (n = 54,418) were defined as individuals newly diagnosed with gastric cancer from January 2004 through December 2009 and who died before December 2012. Cases were matched with controls (subjects who were alive on the date of death of the corresponding case subject, n = 217,672) for year of entry into the study cohort, age, sex, and socioeconomic status. Odds ratios (ORs) and 95% confidence intervals (CIs) were obtained via conditional logistic regression analysis. Compared with subjects who had never been screened, the overall OR for dying from gastric cancer among ever-screened subjects was 0.79 (95% CI, 0.77–0.81). According to screening modality, the ORs of death from gastric cancer were 0.53 (95% CI, 0.51–0.56) for upper endoscopy and 0.98 (95% CI, 0.95–1.01) for UGI series. As the number of endoscopic screening tests performed per subject increased, the ORs of death from gastric cancer decreased: 0.60 (95% CI, 0.57–0.63), 0.32 (95% CI, 0.28–0.37), and 0.19 (95% CI, 0.14–0.26) for once, twice, and 3 or more times, respectively. Within the Korean National Cancer Screening Program, patients who received an upper endoscopy were less likely to die from gastric cancer; no associations were found for UGI series.